1996
DOI: 10.1074/jbc.271.17.10023
|View full text |Cite
|
Sign up to set email alerts
|

Growth-associated Protein-43 (GAP-43) Facilitates Peptide Hormone Secretion in Mouse Anterior Pituitary AtT-20 Cells

Abstract: The neuronal growth-associated protein (GAP)-43 (neuromodulin, B-50, F1), which is concentrated in the growth cones of elongating axons during neuronal development and in nerve terminals in restricted regions of the adult nervous system, has been implicated in the release of neurotransmitter. To study the role of GAP-43 in evoked secretion, we transfected mouse anterior pituitary AtT-20 cells with the rat GAP-43 cDNA and derived stably transfected cell lines. Depolarization-mediated beta-endorphin secretion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 80 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…The cells were transfected with GAP-43 cDNA. Potassium-stimulated release of -endorphin was greatly enhanced in those cells expressing GAP-43, without a significant change in calcium influx, while corticotropin-releasing factor-evoked hormone secretion was not affected [32]. The transfected cells also showed extended processes when plated on laminin-coated substrates [32].…”
Section: Gap-43 Neurotransmitters and Pharma-cological Agentsmentioning
confidence: 91%
See 2 more Smart Citations
“…The cells were transfected with GAP-43 cDNA. Potassium-stimulated release of -endorphin was greatly enhanced in those cells expressing GAP-43, without a significant change in calcium influx, while corticotropin-releasing factor-evoked hormone secretion was not affected [32]. The transfected cells also showed extended processes when plated on laminin-coated substrates [32].…”
Section: Gap-43 Neurotransmitters and Pharma-cological Agentsmentioning
confidence: 91%
“…Potassium-stimulated release of -endorphin was greatly enhanced in those cells expressing GAP-43, without a significant change in calcium influx, while corticotropin-releasing factor-evoked hormone secretion was not affected [32]. The transfected cells also showed extended processes when plated on laminin-coated substrates [32]. Angiotensin II, when binding to the angiotensin type 1 receptor, increased GAP-43 expression and neurite extension [101].…”
Section: Gap-43 Neurotransmitters and Pharma-cological Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported recently that forced expression of neuromodulin in mouse anterior pituitary AtT-20 cells enhanced K ϩ -evoked hormone secretion and induced changes in cellular morphology (59). These results suggested that AtT-20 cells would be a useful experimental system to explore the molecular mechanism(s) of neuromodulin action.…”
mentioning
confidence: 93%
“…The original AtT-20 cells were transfected using the LipofectAMINE reagent, according to the manufacturer's instructions as described previously (59). Permanent transfected cell lines were selected in medium containing 400 g/ml G418.…”
mentioning
confidence: 99%